Significados e níveis de felicidade em idosos institucionalizados - Reichert, Camila (2019)
The objective of this work was to investigate the meanings attributed by institutionalized elders to the concepts of what is to be happy in old age, as well as the associations between meanings and levels of happiness, where levels were given through the subjective happiness scale and the scale analogue of self-perception of happiness. METHODS: A multicenter cross-section study was caried out in the city of Passo Fundo, Carazinho and Bento Gonçalves, which had 490 institutionalized elderly people, where 125 elderly people met the eligibility criteria for this research on happiness in the elderly institutionalized whit punctuation above the cut grade in the mini mental state examination adjusted for level of schooling. The variable meanings related to the concepto of “whats is to be happy inold age” has been subjected to contente analysis. The scalar data submitted to descriptive analysis, with measures of frequency, position and dispersion. The categorical data were submitted to comparative analyzes that took into account their proportion, as well as the ordinal, their distributions compared between the variables. For these analyzes the chi-square and exact tests of FISHER and Mann-Withey and Kruskal Wallis were used. The open answers submitted to content analysis were integrated the statistical analyzes mediated by the same tests cited. And finally, we performed association analyzes between the scalar data and the categorical data results of the content analysis. The results of these data were subjected to descriptive statistical analyzes and comparisons were made between the frequencies of the different groups established by the design (gender, age and institutionalization time).